Canada, aerial view of mountains, Ellesmere Island - Byrd, Richard Evelyn, 1888-1957 (1925)
Taken from an altitude of about 3000 feet by Byrd on McMillan Arctic Expedition showing the top of some of the rugged snow-covered mountains of Ellsmere Island, north-west of Etah. Though the low-lands were free of snow, the highland is eternally covered with snow. This photograph was taken in August 1925. There were very few landing-places in this region on the summer snow.